PENGEMBANGAN PERPUSTAKAAN SEBAGAI SUMBER BELAJAR DI MTs MALNU PUSAT MENES - Reza Muhammad Syaban (Tarbawi, 2017)
This research aims to describe: 1) Planning of school library development; 2) An overview of the ideal school library as a learning resource; 3) Improve attractive habits for students. The study was conducted at the Madrasah Tsanawiyah Mathlla'ul Anwar Linahdotil Ulama (MALNU) Menes Center. The research method uses qualitative case studies. The research instrument uses human instruments. Data analysis techniques include: Data collection, data reduction, and data reduction. The results of the study: 1) Library The role of library managers also has a very important role for the development of library libraries to develop library support, motivation and creativity of library managers, even if the funding increases, library managers do not have three things there so that the library will walk in place. 2) To make the ideal library must depart from the school itself, then even in building an ideal library cannot be considered, therefore the development of library materials must be adapted to the needs of students who want to improve the curriculum and extra-school curriculum. 3) In increasing reading interest students must be able to motivate students to ask for reading interest. Students can increase students' interest in reading since the beginning need to increase the participation of all educators in educating students about the need to read. Keywords. school library, ideal, reading habits.